A Spatial Modeling Approach for Optimizing the Locations of Large-Scale Biogas Plants from Livestock Manure in Bangladesh - Zinat Mahal; Helmut Yabar (Land)
Since manure sources are widely dispersed and the disposal of manure in landfills or its direct application onto soil is often restricted by laws in many countries, selecting suitable sites for manure management facilities is an important step for sustainable livestock farming. The main purpose of this study is to explore suitable locations for situating large-scale biogas plants from livestock manure in Bangladesh using spatial modeling. This study analyzed land suitability based on several geographical, topographical, environmental, and socio-economic criteria, which were also optimized by reflecting optimum transportation distances from manure sources to the chosen sites using GIS (Geographic Information System) network analysis. Then, the environmental benefits of selected biogas plants were estimated through mathematical equations. It was found that 475, 15, and 68 large-scale biogas plants were spatially possible from large-animal, small-animal, and poultry manure, respectively, to produce a total electricity of 7682.72 GWh (gigawatt) in 2023. By implementing the proposed scenarios, renewable energy production will be increased in Bangladesh by at least 8.69%, and GHG (greenhouse gas) emissions will be reduced by approximately 6636.09 gigagram CO2eq by disposing of 90.14 million tons of manure each year. Hence, the potential selection of biogas plant locations and benefit analysis of different scenarios will guide the establishment of a local decision for the utilization of regional bioenergy from livestock manure in Bangladesh.